The Herd Health Handbook for Goat Producers: Food Safety at the Farm Gate: A Holistic Approach to Food Safety and Herd Health - Ray Mobley; Carmen Lyttle-N’guessan (EDIS)
FAMU007, a 2-page fact sheet by Ray Mobley and Carmen Lyttle-N'guessan, provides an overview of the science-based strategies for ensuring food safety at the producer level. Published by Florida A & M University Extension, September 2009.